Pemanfaatan Web Aplikasi Pembelajaran Teintegrasi Artificial Intelligent untuk Meningkatkan Keterlibatan Belajar Siswa - Winanti, Winanti; Prihastomo, Yoga; Prabowo, Yulius Denny; Sidik, Achmad; Hendriyati, Penny; Luthfian, Muhamad; Setiawan, Rizky; Wardiansyah, Wardiansyah; Isbah, Latif Palikal (JPM: Jurnal Pengabdian Masyarakat, 2025)
The use of artificial intelligence (AI) technology in education is unavoidable and undeniable. It is a tool that can help teachers and students generate creative and innovative ideas. However, this does not mean that every school is adopting AI technology for various reasons, including teacher concerns about student dependency if continuously using AI. Learning becomes biased and it is impossible to determine whether students' personal results or AI results are the result, so many teachers are still reluctant to use AI. The aging of teachers and poor internet network infrastructure in some schools are among the factors that hinder the use of AI for learning. The purpose of utilizing this AI-integrated learning web application is to assist teachers and students in interactive learning with AI technology so that student engagement in learning continues to increase. The method used in this activity was an interview method with domain experts and potential users. To obtain direct data, focus group discussions (FGDs) and several sharing sessions were conducted through interactive discussions with several teachers, students, and school administrators. In addition, to support this activity, system trials and validation were conducted with teachers and students. The result of this activity is an interactive learning platform named InsanAI. This learning web application will be implemented in several schools and universities, while maintaining academic ethics. It is also hoped that this activity will provide teachers and school administrators with an understanding of the ease and benefits of using AI technology and help students increase their engagement in learning.